GE_GERICHTE P/12331/2011 vom 22. Juni 2017 - GE Cour de justice (2017)
HONORAIRES ; PRESCRIPTION ; RENONCIATION(SENS GÉNÉRAL) ; CALCUL DU DÉLAI ; PRINCIPE DE LA BONNE FOI | CO.128; PPMin.3; CPP.3; CPP.135